Lesbian, gay, bisexual and transgender people's attitudes to end‐of‐life decision‐making and advance care planning. (October 2015) - Hughes, Mark; Cartwright, Colleen
Abstract : Aim: To examine lesbian, gay, bisexual and transgender (LGBT) people's attitudes to advance care planning (ACP) options and alternative decision‐making at the end of life. Method: Three hundred and five LGBT people completed an online or paper‐based questionnaire, comprising fixed‐choice questions and open‐ended questions. Results: Most respondents, particularly those identifying as female or transgender, preferred a partner to be their alternative decision‐maker at the end of life should the need arise. Fifty‐two per cent of respondents had spoken to this person about their wishes. Regarding legal options enabling end‐of‐life decision‐making, 29% had an enduring power of attorney, 18% an enduring guardian and 12% an advance care directive. Conclusion: Despite the significance of ACP for promoting the rights of LGBT people at the end of life, the take‐up of these options was nearly as low as for the general population. The potential for targeted strategies to increase the take‐up of ACP is identified.